2021
DOI: 10.2147/ijgm.s332890
|View full text |Cite
|
Sign up to set email alerts
|

Facilitate Signing with the Family Doctor: A Study of the Practice in Shanghai, China

Abstract: Background: In the time since primary care was implemented in China in 2009, programs of promoting residents signing with family doctor services have been key. However, there has been a lack of effective evaluation of its implementation. Methods: We used mixed methods for evaluating existing measures of facilitating signing with family doctors in Shanghai. Based on the Donabedian model, qualitative informant interviews were conducted to obtain experts' evaluations in aspects of team construction (structure) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Our study found that regular hypertension follow-up management was positively associated with contracting family doctor services among older adults. Older adults with regular hypertension follow-up management preferred to sign family doctor contract services, which was similar to the findings of previous studies on primary health services [ 36 , 37 ]. This result can be explained in terms of both supply and demand characteristics of health services.…”
Section: Discussionsupporting
confidence: 90%
“…Our study found that regular hypertension follow-up management was positively associated with contracting family doctor services among older adults. Older adults with regular hypertension follow-up management preferred to sign family doctor contract services, which was similar to the findings of previous studies on primary health services [ 36 , 37 ]. This result can be explained in terms of both supply and demand characteristics of health services.…”
Section: Discussionsupporting
confidence: 90%
“…And it gains low acceptance by patients especially older adults who are unfamiliar with information technology ( 48 ). With the increasing population and older adults, the total amount of family doctors was insufficient ( 49 ). In terms of the development of an integrated healthcare system, it was limited by the inadequate technical level of secondary or primary services centers ( 11 ), the fragmented governance, and incoordination of healthcare resources in China ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“… 87 The contract between the family doctor and the service provider and the service content needs to be improved. 88 National government factors are the main trigger for family contract services. Public health services provided by family doctors should be included in the scope of health insurance and linked to health insurance to assist family doctor health management.…”
Section: Discussionmentioning
confidence: 99%